if QX=xy/2, px=xz/2 and qx=px than show that xy=yz
Answers
Answered by
3
acc to question,
qx = xy/2 and px = xz/2 and qx=px which means we can write,
xy/2 = xz/2 . Now from both the sides we can see the 2 in the denominator gets cancelled and we are left with the expression as : xy = xz which is the required expression to be proved. Hence proved.
Basically what we have used here is the concept of substitution method i.e. we have substituted the equation in mid with it's equivalent value.
qx = xy/2 and px = xz/2 and qx=px which means we can write,
xy/2 = xz/2 . Now from both the sides we can see the 2 in the denominator gets cancelled and we are left with the expression as : xy = xz which is the required expression to be proved. Hence proved.
Basically what we have used here is the concept of substitution method i.e. we have substituted the equation in mid with it's equivalent value.
Answered by
7
Please try to post complete question.
I hope correct question is:
In the figure, If QX=xy/2, px=xz/2 and qx=px than show that xy=yz
Solution:
In figure:
Qx=1/2xy
xy=2Qx --------equation(1)
Now Px= 1/2 xZ
xZ=2Px ------------equation(2)
Now given Qx=xP
Now substitute the above value in equation 2 we get:
xZ=2Qx------equation (3)
Equating equation 1 and 3
We get
xy=xz
Hence proved
I hope correct question is:
In the figure, If QX=xy/2, px=xz/2 and qx=px than show that xy=yz
Solution:
In figure:
Qx=1/2xy
xy=2Qx --------equation(1)
Now Px= 1/2 xZ
xZ=2Px ------------equation(2)
Now given Qx=xP
Now substitute the above value in equation 2 we get:
xZ=2Qx------equation (3)
Equating equation 1 and 3
We get
xy=xz
Hence proved
Attachments:
![](https://hi-static.z-dn.net/files/d66/aaf6476563887605530678f861784b7e.jpg)
Similar questions